Hypoxia‐induced tRNA‐derived fragments, novel regulatory factor for doxorubicin resistance in triple‐negative breast cancer. Issue 6 (26th October 2018) - Cui, Yangyang; Huang, Yue; Wu, Xiaowei; Zheng, Mingjie; Xia, Yiqin; Fu, Ziyi; Ge, Han; Wang, Shui; Xie, Hui
Abstract: Triple‐negative breast cancer (TNBC) is an aggressive subtype of epithelial breast malignancy, and chemoresistance is the major obstacle for cancer therapy. TNBC is associated with a hypoxic phenotype, and hypoxia contributes to the chemoresistance in breast cancer. Transfer RNA‐derived fragments (tDRs) represent a new class of small noncoding RNAs that can be induced specifically by hypoxia. Here, we conducted a comparative analysis of the aberrant expression of tDRs in hypoxia‐treated TNBC cell lines through the use of high‐throughput sequencing technique. Quantitative real‐time polymerase chain reaction was used to validate the differently expressed tDRs between two samples. The results showed that tDR‐0009 [derived from transfer RNA (tRNA) Gly‐GCC‐1‐1 ] and tDR‐7336 (derived from tRNA Gly‐GCC‐1–2 ) were significantly upregulated when the SUM‐1315 cell lines were stimulated by hypoxia. Gene ontology (GO) and pathway analysis indicated that these two upregulated tDRs were mainly involved in maintenance of stem cell population and cellular response to interleukin (IL)‐6, which may be the underlying mechanism of hypoxia‐induced tDRs that facilitate the doxorubicin resistance in TNBC. The protein–protein interaction network for predicted target genes established by the STRING database manifested that tDR‐0009 (tDR‐7336) might be involved in the chemoresistance of TNBC via regulation of the activation of phosphorylation of STAT3. In summary, our study provided a comprehensive analysis of the deviant expression profiling of tDRs in hypoxia‐treated TNBC cell lines. Specific tDRs may be a new class of regulatory factors involved in the hypoxia‐induced chemoresistance in TNBC, and they could serve as potential biomarkers and intervention targets. Abstract : Triple negative breast cancer (TNBC) is associated with a hypoxic phenotype, and hypoxia contributes to the chemoresistance in breast cancer. Transfer RNA‐derived fragments (tDRs) represent a new class of small noncoding RNAs that can be induced specifically by hypoxia. We provided a comprehensive analysis of the deviant expression profiling of tDRs in hypoxia‐treated TNBC cell lines. Specific tDRs may be a new class of regulatory factors involved in the hypoxia‐induced chemoresistance in TNBC, and they could serve as potential biomarkers and intervention targets.